Characterization of N6-Methyladenosine in Domesticated Yak Testes Before and After Sexual Maturity - Wang, Xingdong; Pei, Jie; Guo, Shaoke; Cao, Mengli; Bao, Pengjia; Xiong, Lin; Wu, Xiaoyun; Chu, Min; Liang, Chunnian; Yan, Ping; Guo, Xian (Frontiers in Cell and Developmental Biology, 2021)
The potential regulatory role of N6-methyladenosine (m6A), the most prominent mRNA modification in eukaryotes, has recently been identified in mammals, plants, and yeast. However, whether and how m6A methylation is involved in sexual maturation in mammals remains largely unexplored. In this study, testicular tissue was obtained from yaks before and after sexual maturation, and m6A maps were generated via preliminary experiments and methylated RNA immunoprecipitation sequencing. Only spermatogonial cells and a few primary spermatocytes were observed in the testicular tissue of yaks before sexual maturation, while spermatogenic cells at different stages of maturity could observed after sexual maturation. Experiments examining the expression of methylation-related enzymes and overall methylation levels showed that the methylation levels in yak testes increased after sexual maturation. Overall, 1438 methylation peaks were differentially expressed before and after sexual maturation; 1226 showed significant up-regulation and 212 showed significant down-regulation after sexual maturation. Annotation analysis showed that the differential methylation peaks were most commonly concentrated in the exon region, followed by the 3'UTR and finally the 5'UTR region. KEGG pathway analysis demonstrated that homologous recombination, the Notch signaling pathway, growth hormone synthesis, and other signaling pathways may be involved in testicular development and maturation in yaks. Levels of most m6A modifications were positively correlated with mRNA abundance, suggesting that m6A plays a regulatory role in mammalian sexual maturation. To our knowledge, this is the first report of an m6A transcriptional map of the yak testes, and our study lays the foundation for elucidating the function of m6A in the development of yak testes.